Varta AG enters new businesses - Costa, Tomás De Menezes Ortigão (2022)
This Work Project was accomplished by a group of Finance students and it simulates the acquisition of a company through a Leveraged Buyout by a Private Equity Fund. The project consists of an Investment Committee Paper (ICP), that consists of a full report of the deal and its projections, usually presented to investors before the Non-binding offer. The proposed target is VARTA AG, a global battery manufacturer and a market leader in certain core segments. Additionally, this company is inserted in a high growing market. The Investment Thesisproposed by the group is, essentially oriented, towards organic growth and is supported by three main value creation strategies: (1) Construction of an EV batteries’ plant, (2) Construction of a batteries’ Recycling facility and (3) Operational Enhancement. Finally, my individual contribution to the overall paper was in the construction of the Business Plan – construction and forecasting of financial statements and business model – the definition of the Capital Structure – how the deal is financed – and the estimation of Returns – distribution of proceeds between the fund and the management team after debt has been fully repaid.